2012
DOI: 10.1007/978-3-642-31037-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Normative Social Influence in Persuasive Technology: Intensity versus Effectiveness

Abstract: It has been established that normative social influence can be used effectively in persuasive technology. However, it is unknown whether the application of more social pressure makes it more effective. To test this hypothesis, a quantitative experiment was conducted on the online social network Facebook. Although evidence to support the hypothesis was found, it cannot be concluded from this experiment that more intense persuasion is more effective, when utilizing normative social influence in persuasive techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Several studies have focused on normative social influence (Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008;Waardenburg, Winkel, & Lamers, 2012). Nolan, Schultz, Cialdini, Goldstein, and Griskevicius (2008) investigated the persuasive effect and detectability of normative social influence and found that normative social influence had a significant effect on group decisions.…”
Section: Social Influence Theorymentioning
confidence: 99%
“…Several studies have focused on normative social influence (Nolan, Schultz, Cialdini, Goldstein, & Griskevicius, 2008;Waardenburg, Winkel, & Lamers, 2012). Nolan, Schultz, Cialdini, Goldstein, and Griskevicius (2008) investigated the persuasive effect and detectability of normative social influence and found that normative social influence had a significant effect on group decisions.…”
Section: Social Influence Theorymentioning
confidence: 99%
“…Social Norm Messages (Normative Influence) Normative social influence can be successfully used in persuasive technologies to alter existing behaviour [49,50]. Social norms refer to the beliefs that individuals hold about others in a social group and what others in that social group do or think [51][52][53].…”
Section: Tunnelingmentioning
confidence: 99%
“…We can often find influence principles applied in several applications, especially oriented to social media [17,25,42,45]. Cialdini wrote a reference book for Influence on people [8].…”
Section: Influence Usermentioning
confidence: 99%